Integrating an CNOP analysis into a deep learning model to identify optimal initial errors for 2020–2022 La Niña prediction - Lingjiang Tao; Rong-Hua Zhang; Wansuo Duan; Lu Zhou; Tiaoye Li (Climate Dynamics, 2026)

Climatological characteristics of tropical cyclones simulated in the global-regional integrated forecasting system (GRIST) model - Xi Cheng; Xinyao Rong; Yi Zhang; Yuqing Wang; Jian Li; Jing Xu (Climate Dynamics, 2025)

Intercomparison of two model climates simulated by a unified weather-climate model system (GRIST), part II: Madden–Julian oscillation - Zhen Fu; Yi Zhang; Xiaohan Li; Congwen Zhu; Hongbo Liu; Xinyao Rong; Chengming Li (Climate Dynamics, 2025)

Atmospheric responses to the interannual variability of sea surface temperature front in the summertime Southern Ocean - Qian-Rong Rao; Li Zhang; Xuya Ren; Lixin Wu (Climate Dynamics, 2024)
Air–sea interactions in mid-latitudes and their climatic effects have long been a research focus. However, the influence of the variability of the Southern Oceanic Front (SOF) on atmospheric processes at interannual timescales remains somewhat ambiguous from existing studies. Using reanalysis data, our findings reveal that the SOF reaches its maximum intensity during the austral summer, characterized by pronounced interannual variability and an insignificant trend. On the one hand, an enhanced SOF intensifies the meridional temperature gradient and atmospheric baroclinicity, accompanied by increased local and downstream baroclinic energy conversion. This amplifies storm track activities in both the lower and upper troposphere. On the other hand, the atmospheric circulation in mid- and high-latitudes exhibits an equivalent barotropic response. This is attributed to the feedback of storm tracks on the mean flow, dominated by the transient eddy vorticity forcing. Moreover, we compare the relative contributions of the South Indian Oceanic Front (SIOF) and South Atlantic Oceanic Front (SAOF) variability to storm track and atmospheric circulation. Results indicate that the SIOF variability dominates the downstream development of storm track response and modulates the anomalous atmospheric circulation around the Antarctic, while the SAOF variability produces only a limited local atmospheric response.

Intercomparison of two model climates simulated by a unified weather-climate model system (GRIST), part I: mean state - Zhen Fu; Yi Zhang; Xiaohan Li; Xinyao Rong (Climate Dynamics, 2024)

An ocean modeling study to quantify wind forcing and oceanic mixing effects on the tropical North Pacific subsurface warm bias in CMIP and OMIP simulations - Yuchao Zhu; Rong-Hua Zhang; Delei Li (Climate Dynamics, 2022)

Impact of Indian summer monsoon on the South Asian High and its influence on summer rainfall over China - Wei Wei; Renhe Zhang; Min Wen; Xinyao Rong; Tim Li (Climate Dynamics, 2014)